DC Universe vs. Masters of the Universe - Giffen, Keith; Bedard, Tony; Kupperberg, Paul (DC Comics, 2014)
"After narrowly escaping his last battle with He-Man, Skeletor has fled to the most unexpected realm to recover: EARTH! Once there, he sets a plan in motion to siphon off Earth's core magic. Forging an unlikely hunting party, He-Man and company go in search of Skeletor and find themselves at odds with the heroes of the DC Universe, He-Man and the Masters of the Universe must find a way to stop Skeletor and his mysterious new master!"--